1994
DOI: 10.1002/aja.1002000403
|View full text |Cite
|
Sign up to set email alerts
|

Murine PGK‐1 promoter drives widespread but not uniform expression in transgenic mice

Abstract: Pgk-1 is an X-linked gene encoding 3-phosphoglycerate kinase, an enzyme necessary in every cell for glycolysis. The regulatory sequences of the Pgk-1 gene were used to drive the E. coli lac2 reporter gene and 2 strains of transgenic animals created with this P g k -l a d transgene carried on autosomes. The levels of expression of Pgk-1 varied from one adult tissue to another and the transgene was similarly regulated. However, in situ staining of the P-galactosidase encoded by the transgene indicated extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…(iii) To achieve transgene expression not only in ES cells but also in differentiated derivatives and tissues of adult animals, we chose the CAG promoter (23), which contains a modified chicken ␤-actin promoter and enhancer sequences from the cytomegalovirus, and the promoter of the PGK. Both promoters have been shown to be ubiquitously active in the mouse (24,25). Three lentiviral vectors were designed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) To achieve transgene expression not only in ES cells but also in differentiated derivatives and tissues of adult animals, we chose the CAG promoter (23), which contains a modified chicken ␤-actin promoter and enhancer sequences from the cytomegalovirus, and the promoter of the PGK. Both promoters have been shown to be ubiquitously active in the mouse (24,25). Three lentiviral vectors were designed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…54,56,[58][59][60] Given the recently demonstrated ability of the Pgk1 promoter to enhance minimal CMV activity in a bidirectional configuration, as well as the hypothesized chromatin insulating properties of dual, divergently transcribed promoters, we postulated that this promoter architecture would increase CMV transcription and prevent variegation in ES and XEN cells. 27,29,36,37 In addition, previous reports comparing promoter activity within ES and hematopoietic progenitor cells indicated that EEF1A1 was the strongest promoter tested.…”
Section: Bidirectional Expression Cassette Designsmentioning
confidence: 99%
“…This has been shown for several oncogenes retrovirally transduced into rat NEC grafts, which continue to proliferate in vivo after grafting. 34 The internal Pgk-1 promoter utilized in our study is active in embryonic and postnatal neural tissues 35 and the pM48 retrovirus construct with the internal Pgk-1 promoter has been shown to be less susceptible to rapid downregulation of retrovirus expression in vivo than LTR-based retrovirus constructs. 22 According to a popular hypothesis, 3 medulloblastomas originate from remnants of the external cerebellar granule cell layer (EGL).…”
Section: Discussionmentioning
confidence: 99%